Socio-economic development of the malays: case of Kampong Sebuyau, Sarawak / Jelani Razali … [et.al.]. - Razali, Jelani; Abdullah, Abdul Jabbar; Jamain, Mohd Sapawi (2008)
Rural development and rural poverty eradication have always been a priority in the Malaysian government development programmes as evidenced by all the previous Malaysian plans. The income gap between rural and urban population still exist as reflected by the incidence of poverty. The rate of rural poverty is still high as compared to urban areas. Though the poverty rate had declined significantly since 1970, rural poverty rate stands at 10% in 2002 as compared to 1.9% in urban area in the same year. In kampong Sebuyau, only 27.31% of the household have income above RM600. Another 72.69 % of households have income between below RM600 per month, which is below the poverty line income for Sarawak. This also indicates that more than 70 % of the households in Kampong Sebuyau were living below the poverty line income. Most of the households in Kpg. Sebuyau do not have agriculture land. Only 38.72% (103) owned agriculture land. This landless problem had jeopardized government effort to uplift the income and economic status of the residents through its land development policy. Looking at the employment pattern, more than 50% of the households have no permanent or regular employment. They work as odd jobs laborers, van operators, boatmen and others. These pattern of employments engaged by the households are mostly low value added and low income activities and has little impact in uplifting their social economic status.